2017
DOI: 10.15587/2312-8372.2017.99941
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of formulation composition of the crispbread with improved consumer properties

Abstract: усоверШенсТвование ик-иЗлучаТеля Для соЗДания беЗреФлекТорной суШилки расТиТельного сырья Усовершенствован ИК-излучатель на основе гибкого пленочного резистивного электронагревателя излучающего типа для создания безрефлекторных ИК-сушилок растительного сырья. Это обеспечит уменьшение металлоемкости оборудования, равномерность распределения тепловых потоков на приемных поверхностях (сетчатых поддонах с сырьем) и повысит качество получаемых сушеных полуфабрикатов. Исследована поглощающая способность растительног… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…where Z(x i ) -target function that reflects the protein mass share in the recipe, g/100 g of the ready product; x i -recipe component, g/100 g. For modeling the recipe mathematically, there was used the method of linear problems, realized by the simplex-method [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…where Z(x i ) -target function that reflects the protein mass share in the recipe, g/100 g of the ready product; x i -recipe component, g/100 g. For modeling the recipe mathematically, there was used the method of linear problems, realized by the simplex-method [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…To carry out the experiment, new spelt-based crispy breads with the inclusion of herbal supplements, which were added separately (fruit powders of milk thistle, mountain ash, rosehip, green tea extract), were used as objects of research. According to the previously calculated recipe [9], all the initial components of the crispy bread were subjected to sieving, magnetic cleaning and dosage. The resulting mixture was sent to a special apparatus for the production of whole-grain expanded grains of the УВХ-80х8 brand (Ukraine), where its thermal and mechanical processing took place at the modes recommended for this equipment: duration 8 s, P=2.5...5 MPa.…”
Section: Methodsmentioning
confidence: 99%
“…The conducted scientific studies confirm the expediency of introducing into the composition of loaves to improve the trace element composition and increase the content of group B vitamins of non-traditional types of flourpea, buckwheat or pumpkin [4,5]. There are also known ways to increase protein, carbohydrates, including fiber, and minerals by using brown algae powder for the preparation of waffle loaves, adding turnip powder or milk thistle powder with a vitamin-mineral mixture to the recipe [6,7,8]. Studies have found that the introduction of apple powder into the recipe of loaves has a positive effect on organoleptic parameters, first of all, the color and aroma of finished products improves [9].…”
Section: Introductionmentioning
confidence: 96%